THEORY OF CREATION AND THE GENETIC INTEGRITY OF THE WORLD – THE FUTURE OF HUMANITY BASIS OF IDEOLOGY - В. A. Astafyev (Модернизация, инновация, развитие, 2015)
Article describes one of the most difficult problems – the Theory of genetic energy-information unity of the World, according to which the World is the single entity hierarchically organized and directed by the World Creator, appearance of the Creator and creation by Him the Basic Genome of the World (BGW). The integral-dynamic formula of the BGW is described. The World Genome manifests the basic idea of the evolution: it is the code for structural and functional organization and evolution of all entities. The World Genome forms the General Laws of the World. The Theory of genetic energy-information unity of the World is proved the general idea – modern crisis can be transformed by realization of genetic energyinformation unity of the World-Natura-Man.